2006
DOI: 10.1007/s10658-006-9052-1
|View full text |Cite
|
Sign up to set email alerts
|

Biological and molecular characterization of laboratory mutants of Cercospora beticola resistant to Qo inhibitors

Abstract: The resistance to strobilurin-related fungicides and its molecular basis in laboratory mutant isolates of Cercospora beticola was investigated. After ultraviolet mutagenesis, mutants with high, moderate or low resistance levels to pyraclostrobin were isolated from a wild-type strain of C. beticola. Fungitoxicity tests on the response of resistant isolates on medium containing pyraclostrobin and salicylhydroxamate (SHAM), a specific inhibitor of cyanide-resistant (alternative) respiration, indicated that the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 33 publications
1
33
1
Order By: Relevance
“…Other evidence suggests that the fungal AOX system is active during infections in planta, but can be inhibited by plant secondary metabolites (Wood and Hollomon 2003). In contrast to our results with F. effusum, no toxic effects of SHAM or PG were reported in previous in vitro studies of several other fungi, including Alternaria solani ( Jones et al 2007;Malandrakis et al 2006;Markoglou et al 2006;Pasche et al 2004;Ziogas et al 2002). However, there are very few examples of such studies that included any biochemical evidence of the suppression of AOX, e.g., measurements of oxygen uptake.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Other evidence suggests that the fungal AOX system is active during infections in planta, but can be inhibited by plant secondary metabolites (Wood and Hollomon 2003). In contrast to our results with F. effusum, no toxic effects of SHAM or PG were reported in previous in vitro studies of several other fungi, including Alternaria solani ( Jones et al 2007;Malandrakis et al 2006;Markoglou et al 2006;Pasche et al 2004;Ziogas et al 2002). However, there are very few examples of such studies that included any biochemical evidence of the suppression of AOX, e.g., measurements of oxygen uptake.…”
Section: Discussioncontrasting
confidence: 99%
“…Due to the inhibition of electron flow through complex III by QoI fungicides, an alternative respiration system located on the mitochondrial membrane can be activated to avoid the fatal effects of the fungicide (Kameko and Ishii 2009;Wood and Hollomon 2003;Ypema and Gold 1999). Therefore, it is a common practice to include alternative oxidase (AOX) inhibitors, e.g., salicylhydroxamic acid (SHAM), in the medium to suppress alternative respiration (Avila-Adame et al 2003b;Avila-Adame and Köller 2003a;Kameko and Ishii 2009;Markoglou et al 2006;Malandrakis et al 2006;Jones et al 2007;Ishii et al 2009;Kim et al 2003;Köller et al 2004;Pasche et al 2004;Steinfeld et al 2001;Walker et al 2009;Wood and Hollomon 2003;Ziogas et al 2002;Ziogas et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Strains of C. arachidicola Hori, C. beticola and C. kikuchii with resistance to methyl benzimidazole carbamate (MBC) fungicides have been reported (Georgopoulos & Dovas, 1973;Clark et al, 1974;Littrell, 1974;Rupel & Scott, 1974;Smith & Littrell, 1980;Bugbee, 1996;Campbell et al, 1998;Weiland & Halloin, 2001;Imazaki et al, 2006). In addition, populations of C. beticola with reduced sensitivity to demethylation inhibitor (DMI) fungicides (Karaoglanidis et al, 2000(Karaoglanidis et al, , 2002Secor et al, 2010), QoI fungicides (Malandrakis et al, 2006;Secor et al, 2010), and triphenyltin hydroxide fungicides (Giannopolitis, 1978;Bugbee, 1995Bugbee, , 1996Campbell et al, 1998) have been reported. Considering the high level of genetic diversity within C. sojina, and the fact that strains of C. sojina and other Cercospora species have been selected with resistance to fungicides, the risk of selecting strains of C. sojina with resistance to additional fungicide classes may be elevated.…”
Section: Resultsmentioning
confidence: 99%
“…Despite its practical relevance, little is known about the fitness cost associated with QoI resistance conferred by the G143A substitution. Fitness penalties have been observed in QoIresistant field isolates of P. grisea and P. viticola, and laboratory mutants of Cercospora beticola (Avila-Adame & Köller, 2003;Malandrakis et al, 2006). In contrast, fitness penalties are not apparent in QoI-resistant field isolates of B. graminis and B. cinerea, and laboratory mutants of Penicillium digitatum (Heaney et al, 2000;Chin et al, 2001;Banno et al, 2009;Zhang et al, 2009 several fungal plant pathogens and to study the impact of the introduction of the G143A substitution on bc 1 complex activity.…”
Section: Evolution and Fitness Costs Associated With Qoi Resistancementioning
confidence: 99%